Quim Monzó i la societat postmoderna. «El perquè de tot plegat»: un comentari de text - Enric Balaguer (Caplletra: Revista Internacional de Filologia, 2015)
A successful columnist and narrator, Quim Monzó deals with human relationships in society at the turn of the century in El perquè de tot plegat. The article analyses the literary mechanisms and the stylistic resources that the work offers.